The Rise of India in Sports: A Mirror to National Pride and Identity - Sumanth S. Hiremath (Randwick International of Social Science Journal, 2026)
This article examines the intricate relationships that exist between Indian national identity and sport, emphasising how widespread participation and sporting accomplishments promote patriotism and a sense of shared national identity. Using a mixed-methods research design and based on Benedict Anderson's theory of "imagined communities", it examines India's sporting development from 1900 to 2025, emphasising the notable increase in Olympic, Commonwealth, and Asian Games medals. Quantitative data supports a 345.7 per cent improvement in Olympic performance after 2000, a growing sports industry projected to reach $130 billion by 2030, and a 23 per cent national sports participation rate. Qualitative insights relate changing manifestations of patriotism to important historical turning points like the hockey golden age and more recent victories like Neeraj Chopra's Olympic gold. According to the findings, sport plays a crucial role in uniting India's diverse population, especially youth involvement, through media representation, shared experiences, and growing economic significance.